The Epidemiology and Ecology of Leishmaniasis - Claborn, David (IntechOpen, 2017)
Leishmaniasis is a vector-borne, parasitic disease with tremendous variety in presentation, biology, and epidemiology. Any book on this disease must acknowledge the nearly impossible task of providing an exhaustive account of leishmaniasis simply because the epidemiology of the disease is so very complex. This book addresses some of this variety with chapters on the epidemiology of leishmaniasis in North Africa, Central America, and South America. The purpose of the book is not to specifically address diagnosis and treatment of the disease, but rather to provide a sample of the differing epidemiologies of leishmaniasis that occur due to variations in local habitats; the presence of different vectors, reservoirs, and agents; and the wide variety of cultures in which this disease occurs.